2013
DOI: 10.1007/s11738-013-1469-5
|View full text |Cite
|
Sign up to set email alerts
|

Copper phytoextraction with Salix purpurea × viminalis under various Ca/Mg ratios. Part 2. Effect on organic acid, phenolics and salicylic acid contents

Abstract: One-year-old cuttings of basket willow (Salix purpurea 9 viminalis) were cultivated hydroponically under increasing Cu concentrations (0, 1, 2 and 3 mM) and at four Ca/Mg ratios (4:1, 1:10, 20:1 and 1:1 / 4 ). After 14 days, rhizosphere and leaf samples were analysed. Salix plants were able to release relatively high amounts of low molecular weight organic acids (LMWOAs) in a short period of time. The total amount of LMWOAs increased with increasing Cu concentrations. Oxalic and acetic acids were dominant, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 59 publications
(68 reference statements)
0
6
0
1
Order By: Relevance
“…A high proportion of positive correlation seems to confirm the important role of LMWOAs in element accumulation known in plants (Drzewiecka et al 2014; Kutrowska and Szelag 2014; Goliński et al 2015). Pearson correlation coefficients ( r ) between the individual organic acid and element contents were also estimated (Table 6).…”
Section: Resultsmentioning
confidence: 62%
“…A high proportion of positive correlation seems to confirm the important role of LMWOAs in element accumulation known in plants (Drzewiecka et al 2014; Kutrowska and Szelag 2014; Goliński et al 2015). Pearson correlation coefficients ( r ) between the individual organic acid and element contents were also estimated (Table 6).…”
Section: Resultsmentioning
confidence: 62%
“…Solutions with higher Mg than Ca can have negative implications on soil structure, infiltration, and hydraulic conductivity (Bame et al, 2013;Yilmaz et al, 2005). The ratio between soil Ca and Mg also affects the behaviour of other nutrients such as phosphorous (Manimel Wadu et al, 2013), nitrogen (Favaretto et al, 2012), and copper (Lombini et al, 2003), as well as plant biomass and nutrient accumulation in tissues (Kopsell et al, 2013;Drzewiecka et al, 2014). The soil Ca:Al ratio is an indicator of ecosystem stress as a result of acid deposition and soil infertility.…”
Section: Introductionmentioning
confidence: 99%
“…A number of willow species and varieties tolerate metal contaminants (such as Cd, Cu, Pb and Zn) relatively well and are able to accumulate high concentrations of these toxic substances [98][99][100] and thus help to restore the desirable soil properties. Gommers et al [101] reported the suitability of the establishment of an SRC willow plantation on radiocaesium-contaminated land.…”
Section: Resultsmentioning
confidence: 99%